2004
DOI: 10.1186/1476-4598-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Colorectal cancers displaying high-degree microsatellite instability (MSI-H) have an improved prognosis compared to microsatellite stable (MSS) cancers. The observation of pronounced lymphocytic infiltrates suggests that MSI-H cancers are inherently more immunogenic. We aimed to compare the gene expression profiles of MSI-H and MSS cancers to provide evidence for an activated immune response in the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…6 Interestingly, in these good-outcome patients, there was also an increase in the immune cells infiltrating the tumor. 14,[23][24][25][26] In this work, we demonstrated that these two events associated with a good CRC prognosis (i.e., HSP110 expression and tumor immunosurveillance) may be linked. Indeed, we showed that HSP110 is secreted by CRC cells and skews the macrophage inflammatory profile.…”
Section: Discussionmentioning
confidence: 94%
“…6 Interestingly, in these good-outcome patients, there was also an increase in the immune cells infiltrating the tumor. 14,[23][24][25][26] In this work, we demonstrated that these two events associated with a good CRC prognosis (i.e., HSP110 expression and tumor immunosurveillance) may be linked. Indeed, we showed that HSP110 is secreted by CRC cells and skews the macrophage inflammatory profile.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to their microsatellite-stable counterparts, MSI+ CRCs have a heightened immune response that is evident macroscopically and at the molecular level [13]. This tumour-specific immune response is caused by antigenic MSI-induced frameshift mRNAs and/or peptides [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained, in part, by the absence of a probeset specific for ascl2 in the earlier Affymetrix GeneChips. However, recently Banerjea et al (2004) observed that the mean expression of ascl2 was 4.3-fold greater in microsatellite stable colorectal cancers compared to cancers with high-level microsatellite instability using Affymetrix HG-U133 GeneChips. To our knowledge, this is the only publication to date that specifically cites ascl2 expression in colorectal cancers and provides external validation for our findings.…”
Section: Discussionmentioning
confidence: 98%